Response of Egg Number to Selection of Different Genotypes of 24-bp Insertion-Deletion Locus in the Promoter of Prolactin Gene of Papua Local Chickens - Mu'in, Muhammad Affan; Lumatauw, Sintje (ANIMAL PRODUCTION, 2021)
This study aims to estimate the response of the number of eggs produced up to 240 days of age (EN240) to the selection of Papua local chickens (PLC) with different genotypes from the 24-bp Indel cPRLp locus. A total of 68 PLCs were taken randomly from several breeders in Manokwari as the basic population for selection (G0). Genotype identification of the 24-bp Indel cPRLp locus was performed G0. Based on the distribution of these genotypes, mating pairs were randomly formed G0-II, G0-DD and G0-ID to produce G1-II, G1-DD, and G1-Control (G0-ID offspring). Heritability of EN240 in G1-II and G1-DD populations were estimated in full-sib (single pairs mating). Individual selection based on breeding value EN240 was carried out on G1-II (♀) and G1-DD (♀) to form the selection generation (GS): GS-II (♀) and GS-DD (♀). Selection was also carried out on G1-II (♂) and G1-DD (♂) based on body weight at 240 days (BW240) to become selected GS-II (♀) and GS-DD (♀) mating partners. GS-Control was also formed through 25% random sampling from G1-Control (♂ and ♀). GS mating resulted in the second generation (G2): G2-II, G2-DD, and G2-Control. Age at first laying (AFL), EN240, and mean egg weight (EWA) in hens of G1, GS, and G2 were recorded. Response to selection for EN240 was calculated by two methods predicted selection response (Rp) and actual selection response (Rr). Both methods of calculation yield positive and high values. In actual response (Rr), PLC in II genotypes group are more responsive to the selection treatment than DD genotype group. Selection increase EN240 impact accelerate of AFL and lower the EWA, because of their negative genetic correlation.